Regional Revenue and Expenditure Budget Management and Good Governance: A Review of the Implementation of Good Governance Principles - Dasep Dodi Dasep Dodi Hidayah; Arifah Rosmayudi; Nidia Rismania Dewi (CV RIFAINSTITUT, 2026)
This research aims to analyze the management of the Regional Revenue and Expenditure Budget and the implementation of good governance principles in the Province of West Java. Through a literature study, this research examines local government financial data at the provincial and regency or city levels all over the West Java area to evaluate the effectiveness of budget management and its conformity with good governance principles. The results of the study indicate a significant decrease in the realization of regional revenue and expenditure across West Java in two thousand twenty-three compared to the previous year and below the established Regional Revenue and Expenditure Budget targets. This decline was influenced by a reduction in Regional Original Revenue and intergovernmental transfers to regions and village funds, which impacted various expenditure components. In addition, there are significant differences in the revenue and expenditure structures between the Provincial Government and the Regency or City Governments in West Java. This highlights the importance of optimizing Regional Original Revenue at the regency or city level to enhance regional fiscal independence. The conclusion is that consistently applying good governance principles at the regency or city level is primary to strengthening strategies for increasing Regional Original Revenue